Theatre for Development and the Dynamics of Human Trafficking Across Nigeria Border Communities: The Example of Seme Community in Badagry - Komolafe, Ayodele Michael; Adeyemi, Olusola Smith (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Trafficking in Persons across local and international borders is an institution that has taken many manifestations. It is a complex and multifaceted illicit business practice that involves multiple conspirators at both national and international levels, hence a huge market for cheap labour and prostitution. The strategies of reducing or eradicating this syndicated business, especially in border communities have been of serious concern to the international bodies. This paper through the prism of Theatre for Development (TfD) explores how theatre could be deployed as a reduction tool in human trafficking. The paper adopts Qualitative Research Method and research instruments such as Key Informant Interview, Homestead Approach, Participatory Observation and Role-Play. Primary data was obtained at Seme border community in Badagry Lagos State while Behaviour Modification Theory was adopted for the research. The findings and conclusion show that most border communities in Nigeria have been neglected by the government in terms of checking the nefarious activities of people involved in human trafficking across borders. The paper recommends that re-orientation of the members of the security agencies to be pro-active in reducing the incidence of human trafficking in border communities. It gives deep insight into the collaborative and integral role of theatre through theatre for development strategies in tackling security concerns through behavioural change and attitudinal reorientation.